Evolution of Bridge Diagnostic Load Testing in the USA - Commander, Brett (Frontiers in Built Environment, 2019)
Driven by advancements in technology, along with the ever-growing demands of our aging infrastructure, structural evaluation through testing has progressed from a number of research endeavors to a full-fledged industry. Guidelines for Non-Destructive Evaluation (NDE) methods, diagnostic load testing, and proof load testing were published by the American Association of State Highway and Transportation Officials (AASHTO) in 2003 and were largely shaped by the technologies that were available in the 1990s. While specifications in subsequent AASHTO bridge evaluation manuals have remained relatively constant over the last 15 years, commercial applications have sprung forth in all areas of field-based bridge assessment. Much of the development has revolved around inexpensive high-speed data acquisition, high-speed wireless communications, and the surge of cloud-based data management. The market of equipment and services has developed around three main camps; NDE, Controlled Load Testing, and Structural Health Monitoring (SHM), with each field having a variety of subcategories. For example, Diagnostic Load Tests and Proof Load Tests are the two primary forms of controlled load testing. Selection of the appropriate tools and methods to solve any bridge assessment is a function of what information is available and the required functional serviceability of the structure. In many cases, a combination of methods must be employed to achieve a complete assessment. As such, the lines between NDE, Testing, and SHM have blurred and have become increasingly integral gears of a larger machine. This article provides a history of the primary field bridge evaluation techniques and includes the driving forces in commercial development. Focus is placed primarily on diagnostic load test methodology; however, a variety of testing methods are outlined to illustrate the best tool for the job, along with the several pros and cons of various testing and monitoring methods. Finally, a glimpse into the future of bridge evaluation is provided based on current trends and emerging technologies.